MENINGKATKAN MINAT BELAJAR PESERTA DIDIK DI KELAS VII.G PADA PEMBELAJARAN PENDIDIKAN PANCASILA MELALUI PENDEKATAN CULTURALLY RESPONSIVE TEACHING (CRT) DI SMP NEGERI 51 PALEMBANG - Wayan Helen Sutra Devi; Puspa Dianti; Laili Linda Hartati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to enhance the learning interest of Grade VII.G students in Pancasila education through the implementation of the Culturally Responsive Teaching (CRT) approach at SMP Negeri 51 Palembang. The research employed a Classroom Action Research (CAR) method conducted over two cycles, involving all 27 students of class VII.G as the subjects. The focus of the lesson was on the topic of appreciating the surrounding environment and local culture. Data collection instruments included a learning interest questionnaire and classroom observation, while the data were analyzed using a qualitative descriptive approach. Based on the results of the questionnaire and classroom observations, it was found that students' interest in Pancasila education was very low. One contributing factor was that the learning process relied solely on textbooks and did not relate the material to the students' own experiences. Therefore, there is a need for more engaging instructional approaches to foster student interest, one of which is the implementation of the CRT approach.